Ecocritical Reading of Postwar Narrative: Ecocide, Trauma, and Nostalgia in Bao Ninh's Vietnam War Novel "The Sorrow of War" - Oktaviani, Pranantika (OKARA: Jurnal Bahasa dan Sastra, 2022)
The impacts of the Vietnam War are not only massive on human lives but also on nature's sustainability. The relationship between humans and nature is seen to be disrupted by the presence of armed conflict. As an anthropocentric issue, war is often seen from the perspective of humanity. This paper analyzes how the ecocritical perspective reveals the effects of war and the connection between humans and the physical environment more thoroughly. As qualitative research, the primary data was obtained based on the relevant passages in the novel and examined using the concept of Ecophobia which defines the negative relationship between humans and nature caused by a lack of consideration toward nature sustainability. This research showed how ecocritical reading of war narrative reveals the existence of ecocide as a form of landscape destruction that affects humans' lives, trauma as a result of estrangement from nature, and a sense of nostalgia resulting from the image of idyllic space in harsh postwar reality. Based on the findings, it is stated that Bao Ninh's writing on Vietnam War displays the interconnection between humans and nature, which is revealed in certain angles of conflicts.